MONEY MARKET: THE ROLE AND IMPLEMENTATION OF ECONOMIC GROWTH IN THE NON-REAL SECTOR - Maulida, Atika Zahra; Purnomo, Agus (University of Darussalam Gontor, 2024)
The decision issued by the government to open community activities after the COVID-19 pandemic can encourage economic growth. The money market includes Bank Indonesia Syariah Certificates, SBIS Repurchase Agreement, Sharia Interbank Money Market Instruments, SBSN Repurchase Agreement, and other securities. This study aims to determine the role and implementation of the money market in the economic growth of the non-real sector through qualitative research methods. The data collection method uses accidental sampling, where the researcher interviews the perpetrators and managers of the Sharia money market. The quantitative approach distributes questionnaires about the role and implementation of money market transactions. The research results on money market products show that they are one of the instruments of financial products that can restore performance and economic growth. Money market product transactions have increased from month to month due to the influence of public interest and investment in money market products. The growth performance of the money market can come from increased revenues, sales, purchases, and transactions. The role and implementation of economic growth through the Islamic money market is government intervention and community contribution.